LEARNING STRATEGIES DURING PANDEMIC: PARENTS’ IDEAS FOR EARLY CHILDHOOD DISTANCE LEARNING - Rijalul Alam, Naufal Ahmad (Journal of Islamic Educational Research, 2021)
The current pandemic period provides new experiences for parents to recognize distance learning methods. However, parents felt overwhelmed in their efforts to support their children’s learning at home. The situation creates new problems for parents who are not very familiar with the realm of technology, which also impacts their role. This article investigates the involvement of parents in assisting children during the COVID-19 pandemic. By the case at Kindergarten (PAUD) Intan Permata Aisyiyah in Surakarta and the data was collected through FGD, observation, and interviews, I concluded that some parents have certain ideas and strategies to make distance learning easy and fun so that children do not feel bored studying at home. The strategies used by parents include: 1) providing scope and summary of the learning material that the child will learn, 2) communicating the learning objectives briefly, 3) providing learning resources, either through reading material in textbooks or on the internet, and 4) flexibility study time.